Reforming international extradition : fairness, individual rights and justice - Kennedy, Sally; Warren, Ian (London, UK : Anthem Press, 2024)
Extradition often priorities international comity and state rights over individual protections. This can create unfairness and concerns about extraditee welfare. Using case studies, this book explores these issues and argues that defendant-centered reforms are needed to adjust these unequal levels of authority.
Includes bibliographical references and index.
Keywords: Extradition; Refoulement